Chemoenzymatic Synthesis of Asymmetrically Branched Human Milk Oligosaccharide Lacto-N-Hexaose - Ooi, Kai-Eng; Zhang, Xiu-Wen; Kuo, Cheng-Yu; Liu, Ying-Jia; Yu, Ching-Ching (Frontiers in Chemistry, 2022)
We herein report the first chemoenzymatic synthesis of lacto-N-hexaose (LNH) by combining chemical carbohydrate synthesis with a selectively enzymatic glycosylation strategy. A tetrasaccharide core structure, GlcNH2β1→3(GlcNAcβ1→6)Galβ1→4Glc, a key precursor for subsequent enzymatic glycan extension toward asymmetrically branched human milk oligosaccharides, was synthesized in this work. When the order of galactosyltransferase-catalyzed reactions was appropriately arranged, the β1,4-galactosyl and β1,3-galactosyl moieties could be sequentially assembled on the C6-arm and C3-arm of the tetrasaccharide, respectively, to achieve efficient LNH synthesis. Lacto-N-neotetraose (LNnH), another common human milk oligosaccharide, was also synthesized en route to the target LNH.